The Anti-diarrheal Activity of the Non-toxic Dihuang Powder in Mice - Shang, Xiaofei; Miao, Xiaolou; Yang, Feng; Li, Bing; Guo, Xiao; Pan, Hu; Zhang, Yu; Zhang, Jiyu (Frontiers in Pharmacology, 2018)
Dihuang powder (DHP) has been used in the traditional Chinese medicine for the treatment of diarrhea in some regions of China. But up to now, the anti-diarrheal activity of DHP haven`t been performed with modern pharmacological technology. This study aims to investigate the quality control, the potential toxicity and anti-diarrheal activity of Dihuang powder in mice. High performance liquid chromatography (HPLC) and thin layer chromatography (TLC) were used to detect five active compounds in DHP for quality control, and the acute toxicity and sub-acute toxicity for 28-day oral administration of DHP were then evaluated. The anti-diarrheal activity was investigated using mouse model. Results showed that the levels of quercetin and berberine in DHP were 0.054 mg/g and 0.632 mg/g, respectively, and atractylodin, matrine and patehouli aleohal were also detected in DHP. At the given doses, DHP was safe in terms of acute and sub-acute toxicity. Meanwhile, DHP exhibited strong anti-diarrheal effects as well as decreased gastrointestinal motility and the secretions induced by Sennae and castor oil in a dose-dependent manner. It could decrease the content of IL-1β, IL-6 and TNF-α in the small intestine, and improve the histopathological changes of small intestine and large intestine induced by Sennae. The antinociceptive and anti-inflammatory activities in vivo also were presented. Based on all of the results, we thought that DHP has anti-diarrheal activity, and could be used to treat diarrhea as well as alleviate the pain and inflammation induced by diarrhea. This study provides a theoretical basis for the clinical use of DHP and may assist in the development of new drugs for the treatment of diarrhea. The mechanism of the anti-diarrheal activity should be investigated in the future.